Perceptions of affiliated youth organizations toward effectiveness of Malaysian Youth Council - Md Nor, Siti Maryam (2016)
Youth Organizations are established organizations with facilities and clubs that provide services and activities for youth. It includes schools, residential facilities, youth groups, faith centers, and recreational or sport clubs; all organizations with the mission of helping young people develop into healthy adults. In Malaysia, the Malaysian Youth Council (MYC) is a national umbrella body for youth organizations. It has more than three million members from 39 affiliates. In the year 2015, there were about 10,307 registered youth organizations in the country. Sadly, it was reported that only about 30% of the organizations were considered active. The main problems in the youth organizations according to some researchers are the political parties, leaders and individuals often use youth organization for their personal gain. In Malaysia, youth organizations have been used as stepping stones to obtain titles that carry status or social value, gain government projects, contracts and funding that offer economic value and access to various position and appointments that have political value; and many other opportunities. Based on observations of the organizations, there are some weaknesses occurred among members. Activities were carry out ad-hoc and not based on the needs of its members, it does not put social agenda as a priority and only a small number of organizations have specific programmes to shape future leaders. The objectives of the study are (1) to identify the level of factors (teamwork, youth development, goals, leadership and international networking) associated with the effectiveness of Malaysian Youth Council (MYC); (2) to identify differences in the factors associated to the effectiveness of MYC (teamwork, youth development, goals, leadership and international networking) based on demographic profile; (3) to identify the relationship between the factors (teamwork, youth development, goals, leadership and international networking) associated to the effectiveness of MYC; and (4) to identify the most dominant factor contribute to the effectiveness of MYC. This study basically used survey method, self-administered questionnaires. The questionnaires were distributed to 1200 respondents who were members of Malaysian Youth Council (MYC). The data collection was done in Peninsular Malaysia and East Malaysia (Sabah). The analysis results showed that all level of the factors associated with the effectiveness of Malaysian Youth Council (MYC) are high. From the results of the study, the researcher found that in terms of the relationship between demographics and the study constructs, race and religion were found to be significant with the study constructs. To achieve the third objective which is to determine the relationship between independent variables and dependent variable, the Pearson correlation analysis was done. All 15 correlations coefficient values were significant at the 0.01 level. Leadership was found to have the strongest and highest positive correlation with one variable, i.e., goals. In this study, a multiple linear regression analysis was used to find the most dominant predictor contribute to the effectiveness of MYC. Based on the dependent variable, „effectiveness of MYC‟, the researcher found that there is a significant relationship between the dependent variable and the independent variables (F= 214.742: p= .000 and Adjusted R Square= 0.673). Four of the independent variables were found to be significant. They are “Youth Development”, “Goals”, “Leadership” and “International Networking”. “International Networking” was the most dominant predictor variable influencing the dependent variable (standardized regression coefficient= 0.601). In order to increase the effectiveness of MYC, the factors need to be used and practice to make sure MYC will be the best youth organization in the future. Based on the results, it can be concluded that MYC has a good relationship with their affiliates. They practice a good teamwork with their affiliates. In this study, there were three limitation which are factors which associated to the effectiveness of MYC, the location which the researcher selected (most of the location were in urban areas) and the races who involved in this study; Malay respondents. This study incorporated selected variables that affect the effectiveness of MYC. Future research might look at other variables or factors such as contribution from the members.